Polydimethylsiloxane (PDMS)-based antibacterial organic-inorganic hybrid coatings - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2013)
UV-curable antibacterial organic-inorganic hybrid coatings were prepared by sol-gel method. Triethoxysilane-terminated poly(dimethylsiloxane) (TESi-PDMS) as a new coupling agent to improve the compatibility between organic and inorganic phases was synthesized. PDMS-based urethane methacrylate oligomer was obtained by reacting isophorone diisocyanate with hydroxyethyl methacrylate and hydroxyl-terminated PDMS. The formulations were applied onto polycarbonate panels and then cured by UV radiation. Physical properties of UV-cured free films such as gel content, stress-strain, and conversion of acrylate double bond were examined. In addition, the antibacterial effects of the coatings were investigated. Nanosilver-containing formulations exhibited high antibacterial effect against Escherichia coli and Staphylococcus aureus. Thermogravimetric analysis indicated that thermal stability of the hybrids was significantly higher than the organic polymer. Contact angle measurement showed that addition of silane precursor increased the contact angle from 95 degrees to 110 degrees.
Keywords: Organic-inorganic hybrid; Poly(dimethylsiloxane); Nanosilver; Antibacterial coating; SHAPE-CONTROLLED SYNTHESIS; SILVER NANOPARTICLES; ESCHERICHIA-COLI; POLYSILOXANE; COPOLYMERS